An Empirical Analysis of the Relationships between CPA Examination Candidate Attributes and Candidate Performance - Dunn, W. Marcus; Hall, Thomas W. (The Accounting Review, 1984)
[This paper reports the results of an investigation into the relationships between certain CPA examination candidates' attributes and these subjects' performance for 280 first-time candidates writing the November 1977 and May 1978 examinations in Texas. Findings indicate that scholastic aptitude test scores, accounting GPA, accounting hours completed, school attended, hours of self-study, and completion of a CPA review course have consistently significant associations with examination performance. Attributes lacking significant associations with examination performance include candidates' work experience, age, and completion of an audit course.]